Induction of endoplasmic reticulum stress under endotoxin tolerance increases inflammatory responses and decreases Pseudomonas aeruginosa pneumonia. Issue 5 (20th June 2018) - Kim, Sena; Joe, Yeonsoo; Park, Se‐Ung; Jeong, Sun Oh; Kim, Jin‐Kyung; Park, Seong Hoon; Pae, Hyun‐Ock; Surh, Young‐Joon; Shin, Jaekyoon; Chung, Hun Taeg
Abstract: Endotoxin tolerance develops in the late phase of sepsis to protect cells from an early hyperinflammatory response. Nonetheless, because it induces an immunosuppressive environment, patients with sepsis in its late phase are affected by secondary infections, particularly bacterial pneumonia. Here, we showed that induction of endoplasmic reticulum (ER) stress leads to activation of glycogen synthase kinase 3β (GSK‐3β) and X‐box–binding protein 1 (XBP‐1) in an inositol‐requiring enzyme 1α (IRE1α)‐mediated manner, which in turn restores the inflammatory response in endotoxin‐tolerant macrophages. Animal and in vitro models of endotoxin tolerance were studied along with a model of LPS‐induced endotoxin tolerance and a model of cecal ligation and puncture (CLP)‐induced endotoxin tolerance. To detect the suppressed inflammatory response during endotoxin tolerance, inflammatory‐cytokine expression levels were measured by quantitative real‐time PCR and an ELISA. Our research revealed that induction of ER stress alleviated lung injury in a septic host infected with Pseudomonas aeruginosa via the activation of GSK‐3β and XBP‐1 in an IRE1α‐mediated manner. Consequently, in the lungs of the septic host infected with P. aeruginosa, symptoms of pneumonia improved and the infecting bacteria were cleared. Thus, for septic patients, determination of immune status may guide the selection of appropriate immunomodulation, and ER stress can be a novel therapeutic strategy restoring the immune response in patients with endotoxin tolerance. Abstract : Induction of ER stress alleviates the lung injury of septic host infected P. aeruginosa via the activation of GSK‐3β and XBP‐1 in an IRE1α‐mediated manner.